Cunduk Mentul sebagai Inspirasi Motif Kain dengan Teknik Laser Cutting pada Penciptaan Ready to Wear Deluxe Bergaya Romantic Edgy - Dianova, Dahlia; Marlianti, Mira; Kurniawan, Hadi (Style : Journal of Fashion Design, 2024)
Cunduk mentul, better known as kembang goyang, is an original Indonesian headdress accessory that symbolizes the blessing of female beauty in the hope of being able to face life wisely. The younger generation does not know the meaning and philosophy of this local wisdom, so there is a need to preserve this cultural heritage. This work aims to create a romantic edgy style deluxe ready to wear fashion with laser cutting technique inspired by the cunduk mentul motif. The shape of cunduk mentul is transformed into a fabric motif with laser cutting technique applied to ready to wear deluxe in romantic edgy style. The methods used are exploration, design, and realization. The hope of this work is to add to the diversity of motif designs and works of Indonesian fashion as well as to add insight and a sense of concern for the younger generation towards the preservation of cunduk mentul accessories. The results of the work were realized in six deluxe ready to wear fashion looks presented in the Fashion Show Jogja Fashion Parade (JFP) 2024.